Analisis Peran Pembelajaran Etika Profesi untuk Menghadapi Perkembangan Industri Desain Grafis: Studi Kasus Kota Bandung - Gennardy, Theo; Ratri, Dianing (Serat Rupa: Journal of Design, 2024)
Graphic designer is a profession with considerable influence and scope of work. This causes the demand for this profession to increase every year. However, graphic design has seen a decline in quality and appreciation. Of course, this condition is very contradictory to the increase in demand. According to the International Council of Design (ICO-D), apart from the quality of competence, this condition can occur because there are still problems with professional ethics. As an area that has informal social conditions even in the work environment, Bandung City is one of the areas that feels the impact. which, Informal attitude makes the formation of a less indifferent attitude to standard things such as work agreements, or a professional attitude when working together with colleagues. This attitude makes the graphic design profession in Bandung City has not received a good enough appreciation from the industry. This research will examine the relationship between professional ethics issues and industry perceptions in Bandung City related to the development of graphic design. Data is taken and processed by triangulating data through several methods. Namely, focus group discussions with academics, practitioners, and students who will complement the literature review obtained. From the results of data analysis, it is known that the ethical problems of the graphic design profession that often occur in Bandung City both among apprentices, intermediates, and seniors are communication problems in the social and work environment. Another insight gained is that the perception of professional ethics by each practitioner is different based on their thoughts and experiences, so a reference about professional ethics needs to be uniform. In addition, it is necessary to instill ethics as early as possible so that it can increase the value of the graphic design profession to the practical industry and service users.